MANAGEMENT OF ABHIGATAJA GRIDRASI (SCIATICA): A CASE STUDY (AYUSHDHARA, 2017)
Sciatica is such a disease, which carry little threat to life but interfere greatly with living. The person who suffers from this disease is particularly handicapped, as person can’t walk, stand or sit properly. Now a day the disease Sciatica is found abundantly. It is mainly found in people who undergo heavy work and road accident cases. Several spine disorders can cause spinal nerve compression and sciatica. Sciatica can result from direct nerve compression caused by external forces to the spine nerve roots. For example motor vehicle accidents etc. may injure the nerves or fragments of broken bone compress the spinal nerves. Even though operation needed it can also be cured by Panchakarma therapy. In the month of February-March we came across eight such cases and solved all of them by Panchakarma therapy. To be notified two of them are accident caused, for an instance one successful Abhigataja Gridrasi (Vaataja) case presentation through Panchakarma. Patient was apparently healthy 4 months (October 2016) back when he met with road traffic accident the patient suffers from severe low back ache and slight cervical pain. Patient was diagnosed as Abhigataja Gridrasi and fruitfully treated by Panchakarma therapies like Patrapinda, Jambeerapinda, Shastikashalipinda sweda and Matrabasti.